Realignment of supply chain for profitability: overcoming the financial challenges of e-retailing in India. (23rd September 2021) - Sangvikar, Balkrishan; Kolte, Ashutosh; Pawar, Avinash; Khadke, Kaustubh
The supply chain profitability is a major concern for organisations due to cost elements involved in the supply chain functions. The financial challenges are more intense in e-retailing business than other sectors where the dependency on the supply chain is highest. The supply chain plays a crucial role in deliberating the cost of product and profitability for the manufacturers, distributors, and retailers. This paper analyses the supply chain issues faced by e-retailers and proposes ways to save cost, improve performance, and cater to the needs of customers. This study has adopted the descriptive research design and conducted interviews of employees, warehousing staff, and delivery associates of e-retail companies (Flipkart and Amazon) to get the inferences. The outcome of the paper signifies the means for cost optimisation, enhancement in operations, and improvement in the delivery performance of e-retail supply chains. It also proposes the cost management model for e-retail supply chains to operate effectively in the Indian environment.